THE SPECIATION IN GENETIC ALGORITHMS FOR PRESERVING POPULATION DIVERSITY AND OPTIMIZATION OF FUNCTIONS WITH SUBOPTIMAL SOLUTIONS - V. Pretsel; Roman Shuvar (Електроніка та інформаційні технології)
Background. Genetic algorithms are used in various tasks and show advantages compared to other optimization methods, which may not always be applicable. However, there are cases when they can’t provide the best possible solution. One of them is the premature convergence of the population to a single solution. As population diversity decreases, the search domain becomes limited, and potential solutions may be overlooked. This scenario is particularly common in multimodal functions where multiple local optima exist. To address this, a class of techniques known as niching techniques has been developed. These methods preserve population diversity and prevent premature convergence to suboptimal solutions.